Concise Encyclopedia of Special Education : A Reference for the Education of the Handicapped and Other Exceptional Children and Adults - Reynolds, Cecil R.[ed] (John Wiley r Sons, 2002)
xviii, 1062 p. : Ill.; 25 cm